Bowel Preparation and Peri-operative Management for Radical Cystectomy in Turkey Turkish Urooncology Association Multicenter Survey - (:unkn) unknown (UROL & NEPHROL RES CTR-UNRC, 2011)
Purpose: To investigate the preferences and practice patterns of urooncologic surgeons in Turkey on bowel preparation and pen-operative management for radical cystectomy. Materials and Methods: This study was conducted by Turkish Urooncology Association as a multicenter survey. Participants were asked to fill in questionnaires dispensed at annual oncologic meeting or using internet access to the website of Urooncology Association. The questionnaire consisted of multiple choice or open-ended questions related to frequency of cystectomy, surgical technique and type of diversion, bowel preparation protocol, nasogastric tube applications, antibiotic prophylaxis, and deep vein thrombosis prophylaxis. Collected data from the survey were presented descriptively. Results: Forty-four questionnaires from 44 surgeons of different centers were evaluated. All participants answered that they always perform bowel preparation before cystectomy. Four participants reported that they had an experience of cystectomy without bowel preparation. Bowel preparation methods included long conservative methods, short enema protocols, and Golytely, but there were significant differences in application of each method. Of participants, 88.6% perform diversion by themselves whereas others ask help from a general surgeon. Antibiotic prophylaxis is preferred mostly by 2 agents using third-generation cephalosporins and metronidazole for a period of 5 days or more in the majority. Type, duration, and dosage of deep vein thrombosis prophylaxis differed among participants. Conclusion: There are significant individual differences in pen-operative management of radical cystectomy, which render deficient and sometimes inadequate patient care. There is a need to establish standard protocols for bowel preparation and adequate pen-operative management for radical cystectomy.
Keywords: urinary bladder neoplasm; urinary diversion; perioperative care; postoperative complications; INVASIVE BLADDER-CANCER; URINARY-DIVERSION; COMPLICATIONS; RECOVERY; TIME; PLAN